Behavioral Correlations Associated with Fear of Humans Differ between Rural and Urban Burrowing Owls - Carrete, Martina; Tella, José L. (Frontiers in Ecology and Evolution, 2017)
Behavioral studies are fundamental to understanding how animal populations face global change. Although much research has centered upon the idea that individuals can adaptively modify their behaviors to cope with environmental changes, recent evidence supports the existence of individual differences in suites of correlated behaviors. However, little is known about how selection can change these behavioral structures in populations subject to different environmental constraints. The colonization of urban environments by birds has been related to their inter-individual variability in their fear of humans, measured as their flight initiation distance to an approaching human, such that urban life would select for fearless individuals. This behavior has been demonstrated to be heritable and highly consistent throughout the adult lifespan of burrowing owls (Athene cunicularia). Here, we experimentally assessed, in field conditions, whether urban life involves changes in other behaviors such as exploration and antipredatory response through their correlation with fear of humans. Breeding urban birds were more fearless toward humans and were quicker to explore a new food resource and defend their nests from predators than their rural counterparts. However, while fear of humans positively correlated with exploration and antipredatory response in the rural population, it only correlated with exploration in the urban one. Predator release in urban environments could relax - and even counterselect - antipredator behaviors, thus dismantling the behavioral correlation existent in natural populations. Altogether, our results suggest that rural and urban animals may differ in some behavioral aspects, may be as a consequence of the selection processes acting during the colonization of urban areas as well as the different ecological environments encountered by individuals.